Spontaneous Superficial Femoral Artery Pseudoaneurysm in Behcet's Disease. (16th April 2014) - Ugurlucan, Murat; Sendil, Selin; Sayin, Omer Ali; Barburoglu, Mehmet; Gok, Emre; Turkyilmaz, Gulsum; Basaran, Murat; Alpagut, Ufuk; Dayioglu, Enver
Abstract : Behcet's disease is an autoimmune multisystemic disorder on vasculitis base. Cardiovascular involvement is the most important predictor of morbidity and mortality. The treatment should be planned carefully for pathologies requiring interventions. In our report, we present a 45-year-old patient with spontaneous superficial femoral artery pseudoaneurysm, our treatment strategy, and circumstances we faced.